Electronic Fetal Monitoring in a Small Hospital. Part 2: Intrapartum Use - Casson, R. Ian (1984)
A case series analysis assessed the intrapartum use of an electronic fetal heart rate monitor at a 40-bed hospital in Newfoundland. Seventy-five patients at risk and 52 patients at no predictable risk were monitored during labor. Fetal distress was the sole reason for cesarean section or instrumental delivery in nine of the group at risk and six of the group at no predictable risk. Of these 15 babies, all had five minute Apgar scores greater than six. Intrapartum monitoring is indicated for patients at risk, either because they develop a problem at a time when transfer to a regional centre is precluded, or because they have been judged safe to deliver at the small hospital.